UNLOCKING DESTINATION APPEAL: A SCALE VALIDATION OF INNOVATION PRACTICES IN FOOD TOURISM CONTEXTS - Alias, Mohd Syaifuddin Mohd; Rani, Zaharah Mohamed; Ariffin, Hashim Fadzil (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
This paper aims to investigate the scale validation of innovation practices, focusing on the tourist destination image in the context of food tourism in Malaysia. By using a quantitative approach, data were collected through various methods, including online and self-administered at KLIA1 and KLIA2 or any other public hub station. A total of 650 responses were obtained from both domestic and international tourists. The data were then analysed by using SPSS to validate the Cronbach’s Alpha for coefficient alpha analysis and exploratory factor analysis (EFA) to measure the validity of item used. To examine the scale validation of innovation practices, the study employs structural equation modelling (SEM). The analysis includes key procedures such as first-order confirmatory factor analysis (CFA) to validate the constructs and its respective items. For this particular procedure, the scale measurement focusing only on innovation practices. Based on the construct, innovation practices were measured by using five dimensions namely; product, service, process, organizational, and marketing innovation. The construct is a crucial part in measuring the relationship between tourist destination image and its influence on food tourism in Malaysia.